Plan de negocios para la creación de un hotel en la isla Santa Cruz, provincia de Galápagos en el periodo 2024- 2028 - Placencia de la Cruz, Jonathan Stalyn (2025)
The business Plan is focused on the establishment of a Hotel in Santa Cruz Island from 2024 to 2028; this document is presented in 5 detailed chapters that address topics from the public as well as the private sector. It includes information such as the geographical location, the number of rooms, the building progress, the requirement of machinery, on the other hand it presents the name of the Company, and the geographical location of overnight facilities in the area. The financial statement evaluates aspects such as: costs, investment, depreciation, amortization, income, break-even point, final statements, projection of cash flow, and furthermore financial evaluations are conducted using metrics such as: the minimum accepted rate of return, net present value and internal rate of return, which helps measuring the profitability of the Business Plan. The main financial indicators are: • Total cost of $112,613.84. • Total investment of $305,679.15. • Break-even point of $97,133.18. • Net income for the first year of $77,613.54. • Internal Rate of Return (IRR) of 28,26%. The recovery period indicates that the fixed investment, the intangible investment and working capital are recovered within 4 years. These results indicate that the hotel not only covers it costs but also generates a positive return on investment, highlighting its financial stability and potential for profitability.